Phenotypic plasticity in sargassum forests may not counteract projected biomass losses along a broad latitudinal gradient - Gouvêa, Lidiane (2022)
Phenotypic plasticity and local adaptation can adjust individual responses to environmental changes across species' ranges. Studies addressing the implications of such traits have been underrepresented in the marine environment. Sargassum cymosum represents an ideal model to test phenotypic plasticity, as populations along the southwestern Atlantic Ocean display a sharp decrease in abundance toward distributional range limits. We (1) characterized the macroecological environment of S. cymosum across a latitudinal gradient, (2) evaluated potential differences in ecophysiological adjustments (biomass, photosynthetic pigments, phenolic compounds, total soluble sugars and proteins, and carbon-nitrogen-CN-content), and (3) tested for differences in thermal tolerance based on time series analyses produced from the present to contrasting representative concentration pathways scenarios (RCP) of future climate changes. Our results showed distinct macroecological environments, corresponding to tropical and warm temperate conditions, driving biomass and ecophysiological adjustments of S. cymosum. Populations from the two environments displayed contrasting thermal tolerances, with tropical individuals better coping with thermal stress when compared to more temperate ones (lethal temperatures of 33 degrees C vs. 30 degrees C); yet both populations lose biomass in response to increasing thermal stress while increasing secondary metabolites (for example, carotenoids and phenolic compounds) and decrease chlorophyll's content, Fv/Fm, total soluble sugars concentration and CN ratio, owing to oxidative stress. Despite evidence for phenotypic plasticity, significant future losses might occur in both tropical and warm temperate populations, particularly under the no mitigation RCP scenario, also known as the business as usual (that is, 8.5). In this context, broad compliance with the Paris Agreement might counteract projected impacts of climate change, safeguarding Sargassum forests in the years to come.